2020
DOI: 10.3390/jpm10010009
|View full text |Cite
|
Sign up to set email alerts
|

“Balancing Expectations with Actual Realities”: Conversations with Clinicians and Scientists in the First Year of a High-Risk Childhood Cancer Precision Medicine Trial

Abstract: Precision medicine is changing cancer care and placing new demands on oncology professionals. Precision medicine trials for high-risk childhood cancer exemplify these complexities. We assessed clinicians' (n = 39) and scientists' (n = 15) experiences in the first year of the PRecISion Medicine for Children with Cancer (PRISM) trial for children and adolescents with high-risk cancers, through an in-depth semi-structured interview. We thematically analysed participants' responses regarding their professional cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 38 publications
(56 reference statements)
5
40
0
Order By: Relevance
“…Together with previous research [ 7 , 9 , 10 , 13 , 14 , 15 , 43 , 44 , 45 , 46 ], our results further emphasize the importance of improving medical education around genetics to train physicians to interpret and communicate genomic information relevant to their practice. In our study, oncologists expressed not feeling practiced or trained at interpreting the genomic results without genetics support.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Together with previous research [ 7 , 9 , 10 , 13 , 14 , 15 , 43 , 44 , 45 , 46 ], our results further emphasize the importance of improving medical education around genetics to train physicians to interpret and communicate genomic information relevant to their practice. In our study, oncologists expressed not feeling practiced or trained at interpreting the genomic results without genetics support.…”
Section: Discussionsupporting
confidence: 85%
“…We have previously reported that prior to participating in ROR sessions, pediatric oncologists believed that returning ES results would be similar to returning results from other medical tests [ 4 ]. However, after participating in ROR, this study found that those same oncologists described feeling they lacked sufficient technical knowledge and training to communicate germline GS results as well as uncertain information in lay terms—similar to challenges identified by non-geneticist physicians in other studies [ 9 , 10 , 13 , 15 , 16 , 20 , 21 , 22 , 23 ]. As a result, oncologists felt that support from GCs and genetic specialists was essential to interpreting and effectively communicating genomic results to families.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…However, there are only a small number of studies investigating these preferences. [10][11][12][13][14][15] Broader research, examining parental decision-making about treatment options for their child with cancer indicates parents are influenced by numerous factors including the child's prognosis and quality of life (QoL), the impact of treatment on the family, as well as cost and funding considerations. 16,17 Several studies have highlighted how these factors influence HCPs and parents differently.…”
Section: Introductionmentioning
confidence: 99%